Phenotypic resistance not associated with knockdown mutations (kdr) in Anopheles albimanus exposed to deltamethrin in southern coastal Ecuador - Sebasthian Real-Jaramillo; Juan J. Bustillos; Ana L. Moncayo; Marco Neira; Leonardo Fárez; Efraín Beltrán; Sofía Ocaña-Mayorga (Malaria Journal, 2024)
Abstract Background Decrease in malaria rates (e.g. incidence and cases) in Latin America maintains this region on track to achieve the goal of elimination. During the last 5 years, three countries have been certified as malaria free. However, the region fails to achieve the goal of 40% reduction on malaria rates and an increase of cases has been reported in some countries, including Ecuador. This scenario has been associated with multiple causes, such as decrease of funding to continue anti-malarial programmes and the development of insecticide resistance of the main malaria vectors. In Ecuador, official reports indicated phenotypic resistance in Aedes aegypti and Anopheles albimanus to deltamethrin and malathion, particularly in the coastal areas of Ecuador, however, information about the mechanisms of resistance have not been yet elucidated. This study aims to evaluate phenotypic response to deltamethrin and its relationship with kdr mutations in An. albimanus from two localities with different agricultural activities in southern coastal Ecuador. Methods The CDC bottle assay was carried out to evaluate the phenotypic status of the mosquito’s population. Sequencing the voltage gated sodium channel gene (VGSC) sought knockdown mutations (kdr) in codons 1010, 1013 and 1014 associated with resistance. Results Phenotypic resistance was found in Santa Rosa (63.3%) and suspected resistance in Huaquillas (82.1%); with females presenting a higher median of knockdown rate (83.7%) than males (45.6%). No statistical differences were found between the distributions of knockdown rate for the two localities (p = 0.6048) which indicates no influence of agricultural activity. Although phenotypic resistance was confirmed, genetic analysis demonstrate that this resistance was not related with the kdr mechanism of the VGSC gene because no mutations were found in codons 1010 and 1013, while in codon 1014, 90.6% showed the susceptible sequence (TTG) and 7.3% ambiguous nucleotides (TKK and TYG). Conclusions These results highlighted the importance of continuous monitoring of resistance in malaria vectors in Ecuador, particularly in areas that have reported outbreaks during the last years. It is also important to elucidate the mechanism involved in the development of the resistance to PYs to propose alternative insecticides or strategies for vector control in areas where resistance is present.